Flow Metal‐Free ArC Bond Formation via Photogenerated Phenyl Cations. Issue 7 (22nd March 2016) - Bergami, Matteo; Protti, Stefano; Ravelli, Davide; Fagnoni, Maurizio
Abstract: A convenient photochemical flow protocol for the formation of aryl‐carbon bonds via photogenerated phenyl cations has been developed. A wide range of phenylated products, including biaryls, allylarenes, 2‐arylacetals and benzyl γ‐lactones, was smoothly synthesized in satisfactory yields under metal‐free conditions. The adoption of a flow reactor often allowed us to adopt higher concentrations of substrates and shorter irradiation times compared to those usually employed in batch systems. Abstract :